Partnerships with NARS for technology transfer - Smalley, M.E. (International Livestock Research Institute, 1998)
The International Livestock Research Institute (ILRI) works through partnerships which are critical for two reasons: for collaborative research on key components and constraints and for the development, testing and transfer of technologies, based on farmer's needs. The ILRI programme designed to strengthen partnerships with NARS has a set of integrated activities, viz, training and training materials development, information products and services and networking. This paper briefly presents ILRI's activities in each of these three areas, and outlines some ways through which NARS and ILRI might together begin to strengthen opportunities for future collaboration in Asia.